Single-Cell RNA Sequencing Identifies Extracellular Matrix Gene Expression by Pancreatic Circulating Tumor Cells - David T. Ting (Cell Reports, 2014)
Circulating tumor cells (CTCs) are shed from primary tumors into the bloodstream, mediating the hematogenous spread of cancer to distant organs. To define their composition, we compared genome-wide expression profiles of CTCs with matched primary tumors in a mouse model of pancreatic cancer, isolating individual CTCs using epitope-independent microfluidic capture, followed by single-cell RNA sequencing. CTCs clustered separately from primary tumors and tumor-derived cell lines, showing low-proliferative signatures, enrichment for the stem-cell-associated gene Aldh1a2, biphenotypic expression of epithelial and mesenchymal markers, and expression of Igfbp5, a gene transcript enriched at the epithelial-stromal interface. Mouse as well as human pancreatic CTCs exhibit a very high expression of stromal-derived extracellular matrix (ECM) proteins, including SPARC, whose knockdown in cancer cells suppresses cell migration and invasiveness. The aberrant expression by CTCs of stromal ECM genes points to their contribution of microenvironmental signals for the spread of cancer to distant organs.